The Influence of E-Service Quality and E-Trust on Lazada Consumers' Buying Interest on Social Media - Fitriani, Mely (Universitas Negeri Makassar, 2021)
This study aims to determine the effect of e-service quality and e-trust on Lazada consumers' buying interest on social media. The method used in this research is quantitative. The population in this study is Lazada consumers on social media. The number of samples used is 100 respondents who are Lazada consumers. The classical assumption test in this study consists of normality test, reliability test, validity test, normality test, multiple correlation analysis, multiple linear regression, T test and F test. The results of data processing are: (1) Partially e-service quality provides positive and significant influence on buying interest. (2) Partially, e-trust has a positive and significant effect on buying interest. (3) Simultaneously, e-service quality and e-trust have a positive and significant effect on buying interest.